2011
DOI: 10.1364/oe.19.002309
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared gas filled photonic crystal fiber laser based on population inversion

Abstract: We demonstrate for the first time an optically pumped gas laser based on population inversion using a hollow core photonic crystal fiber (HC-PCF). The HC-PCF filled with 12C2H2 gas is pumped with ~5 ns pulses at 1.52 μm and lases at 3.12 μm and 3.16 μm in the mid-infrared spectral region. The maximum measured laser pulse energy of ~6 nJ was obtained at a gas pressure of 7 torr with a fiber with 20 dB/m loss near the lasing wavelengths. While the measured slope efficiencies of this prototype did not exceed a fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(54 citation statements)
references
References 28 publications
4
50
0
Order By: Relevance
“…At total C 2 H 2 pressures as high as 7 Torr, lasing from collisionally populated rotational levels did not occur. 51 Given the short duration of the excitation and output pulses, the absence of lasing from collisionally populated levels is consistent with the RET rate constants given in Tables II and IV. For future development of the laser, the rate constants obtained in the present study should facilitate the computational design of systems that employ long-pulse or continuous wave excitation.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…At total C 2 H 2 pressures as high as 7 Torr, lasing from collisionally populated rotational levels did not occur. 51 Given the short duration of the excitation and output pulses, the absence of lasing from collisionally populated levels is consistent with the RET rate constants given in Tables II and IV. For future development of the laser, the rate constants obtained in the present study should facilitate the computational design of systems that employ long-pulse or continuous wave excitation.…”
Section: Discussionsupporting
confidence: 78%
“…50,51 On pulsed laser excitation of the (1,0,1,0 0 ,0 0 ) R(7) line, Nampoothiri et al 50 observed lasing on the (1,0,1,0 0 ,0 0 ) → (0,0,1,0 0 ,0 0 ) R(7) and P(9) lines. At total C 2 H 2 pressures as high as 7 Torr, lasing from collisionally populated rotational levels did not occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If atomic vapor cells could be integrated with optical fibers or into silicon or silicon nitride photonic circuits, the complexity and functionality of chip-scale atomic devices could be increased considerably. Thermal atomic vapors can be loaded around tapered fibers 251 or into hollow-core optical fibers 110,[252][253][254][255][256][257][258] or hollow waveguides on a chip. 111,259 This allows for long interaction lengths, while maintaining strong transverse confinement, which can be useful for low-power non-linear optics.…”
Section: A Integration Of Atoms and Photonicsmentioning
confidence: 99%
“…The hollow-core optical fibre gas laser (HOFGLAS) -proposed and demonstrated by Jones/Nampoothiri [30,31] -combines the attractive properties of compactness, long interaction length and low lasing threshold of fibre laser and potential for high power and narrow line-width of gas laser. The lasing medium is optically pumped gas molecules filled in hollow-core (HC) photonic crystal fibre.…”
Section: Hollow-core Optical Fibre Gas Lasermentioning
confidence: 99%